Europa ohne Nationen. Robert Menasses Beitrag zur Gestaltung der Europäischen Union der Zukunft in „Die Hauptstadt“ - Jaśkiewicz, Grzegorz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Discussions on the condition of Europe and on the European idea among intellectuals, especially German-speaking writers, have a long and rich history. Goethe and Schiller already spoke about in the 18th century and Novalis in the 19th century, the latter pointing to the European cultural community. After the experiences of the First and Second World Wars, of the cruelty and barbarity of warfare, of dehumanization and mass murder, the discussions on the essence of Europe revived. Richard Nikolaus Coudenhove-Kalergi and Heinrich Mann suggested the creation of a European Community which, although far from today’s European Union, in theory was supposed to serve as a protection against the repetition of nationalism and wars. In 1992 the European Union was founded on the groundwork of the EEC. Austrian-born Robert Menasse is another German-language writer who actively defends the European Union by proclaiming radical views, namely the departure from the nations and the creation of the Republic of Europe. His 2017 novel Die Hauptstadt (The Capital), awarded the Deutscher Buchpreis (German Book Prize) literary prize, is a tribute to Europe and an important contribution to the discussion on the European community and its future. Through the mouth of his alter ego in the novel, Prof. Alois Erhart, Menasse calls for the rejection of the attachment to nations and the creation of Europe of Regions. The book is basically the first European novel (about the European Union) by a German-writing author with such a progressive message. In the novel, the author, shows, against the background of the life of EU officials in Brussels, the reality of Europe, the understanding of national and European identity and the burden of the Holocaust and the bestiality of nationalism for contemporary Europeans. The present paper discusses these views and inscribes them in the long lasting debate on Europe, indicating at the same time the progressiveness of the European idea.

Dyskusje o stanie Europy i idei europejskiej wśród intelektualistów, zwłaszcza pisarzy niemieckojęzycznych, mają swoją długą i bogatą historię. Już w XVIII wieku głos zabierali Goethe i Schiller, w XIX Novalis, który wskazywał na kulturową wspólnotę europejską. Po doświadczeniach I i II wojny światowej, okrucieństwie i barbarzyństwie działań wojennych, odczłowieczeniu i masowych mordach dyskusje nad istotą Europy odżyły. Richard Nikolaus Coudenhove-Kalergi czy Heinrich Mann zaproponowali wspólnotę europejską, która wprawdzie daleka była od dzisiejszej Unii Europejskiej, ale w teorii miała stanowić zabezpieczenie przed powtórką nacjonalizmów i wojen. W 1992 powstała Unia Europejska na podwalinach EWG. Pochodzący z Austrii Robert Menasse jest kolejnym pisarzem niemieckojęzycznym, który aktywnie występuje w obronie Unii Europejskiej, głosząc radykalne poglądy odejścia od narodów i stworzenia Republiki Europy. Jego powieść z 2017 roku pt. „Die Hauptstadt” [Stolica], uhonorowana nagrodą literacką Deutscher Buchpreis [Niemiecka Nagroda Książkowa], jest hołdem złożonym Europie i jednocześnie ważnym przyczynkiem w dyskusji o wspólnocie europejskiej i jej przyszłości. Ustami swego alter ego w powieści, prof. Aloisa Erharta, postuluje Menasse odrzucenie przywiązania do narodów i stworzenie Europy Regionów. Książka jest w zasadzie pierwszą powieścią europejską (o Unii Europejskiej) autora niemieckojęzycznego, w dodatku z tak postępowym przesłaniem. W powieści autor na tle życia urzędników unijnych w Brukseli ukazuje rzeczywistość europejską, pojmowanie tożsamości narodowej i europejskiej i obciążenie współczesnych Europejczyków doświadczeniem holokaustu i bestialstwa nacjonalizmów. Prezentowany artykuł omawia te poglądy i wpisuje je w anonsowaną już wielusetletnią debatę o Europie, wskazując na progresywność idei europejskiej.
Europe without Nations. Robert Menasse’s Contribution to the Shaping of European Union’s Future in the Novel “Die Hauptstadt”
Europa bez narodów. Roberta Menasse wkład w kształtowanie przyszłości Unii Europejskiej w powieści „Die Hauptstadt”
Keywords: Robert Menasse; Europe; European Union; Europe of Regions; novel about Europe; talking about Europe; nationalism; German-language literature; 21st-century Austrian novels; Europa; Unia Europejska; Europa Regionów; powieść o Europie; debata o Europie; nacjonalizm; literatura niemieckojęzyczna; powieść austriacka XXI wieku